The effect of wordwall-based interactive learning media on students’ academic achievement in akidah akhlak: a study at madrasah tsanawiyah 6 sragen - Riska Agustin; Sukari; Ngatmin Abbas (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
The digital transformation in education demands teachers to innovate by utilizing learning media that are not only engaging but also capable of enhancing students' academic performance. One such emerging medium is Wordwall—an interactive, game-based educational platform that is easily accessible. This study aims to examine the effect of using Wordwall-based interactive learning media on students' learning achievement in the Akidah Akhlak subject at MTs Negeri 6 Sragen. The research employed a quantitative method with a quasi-experimental design using a Nonequivalent Control Group Design approach. The sample consisted of 50 students divided into experimental and control groups. Data were collected through pretests, posttests, observation, and documentation. The findings revealed a significant difference in posttest scores between the experimental group (mean = 84.64) and the control group (mean = 73.20). The experimental group also showed higher improvements in affective and psychomotor domains. These results indicate that Wordwall is not only effective in enhancing cognitive learning outcomes but also encourages active participation, positive attitudes, and skill development among students. The implication of this study is the necessity for structured training and integration of interactive digital media into Islamic religious education to improve its effectiveness and appeal.